2015
DOI: 10.3766/jaaa.14093
|View full text |Cite
|
Sign up to set email alerts
|

Refining Stimulus Parameters in Assessing Infant Speech Perception Using Visual Reinforcement Infant Speech Discrimination: Sensation Level

Abstract: Background Speech perception measures have long been considered an integral piece of the audiological assessment battery. Currently, a prelinguistic, standardized measure of speech perception is missing in the clinical assessment battery for infants and young toddlers. Such a measure would allow systematic assessment of speech perception abilities of infants as well as the potential to investigate the impact early identification of hearing loss and early fitting of amplification have on the auditory pathways. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 29 publications
1
25
1
2
Order By: Relevance
“…Recent research has shown that measurements of objective auditory evoked potentials could reveal speech discrimination abilities in infants and young children (Cheour-Luhtanen et al, 1995; Cone, 2015; Small et al, 2017). Other research groups have demonstrated the use of behavioural measures of discrimination by using a visual reinforcement paradigm (Uhler et al, 2015). Our current research builds on these approaches, with the ultimate goal of developing clinical tools to identify infants with hearing loss who may have deficits in speech discrimination despite optimal amplification.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has shown that measurements of objective auditory evoked potentials could reveal speech discrimination abilities in infants and young children (Cheour-Luhtanen et al, 1995; Cone, 2015; Small et al, 2017). Other research groups have demonstrated the use of behavioural measures of discrimination by using a visual reinforcement paradigm (Uhler et al, 2015). Our current research builds on these approaches, with the ultimate goal of developing clinical tools to identify infants with hearing loss who may have deficits in speech discrimination despite optimal amplification.…”
Section: Discussionmentioning
confidence: 99%
“…Two naturally produced vowel sounds, /i/ (“ee” as in “bee”) and /a/ (“ah” as in “law”) were recorded from a female talker (Uhler et al, 2011, 2015) and used as the contrasting stimuli in both the MMR and ACC preparations (Figure 1). Speech stimuli were digitally edited and pitch-matched using the Adobe Audition CC 2015 (Adobe Systems Inc., San Jose, CA) and Melodyne (Celemony Software, Munich, Germany) audio editing platforms.…”
Section: Methodsmentioning
confidence: 99%
“…Data were collected for 43 children aged 7 to 28 months ( M =13.91, SD =5.81). The data for the 21 children with NH were previously reported (Uhler et al, 2015). The 22 infants with bilateral sensorineural hearing loss had losses ranging from mild to profound.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent VRISD study Uhler et al (2015) showed that the level at which NH infants successfully discriminated /a-i/ and /ba-da/ ranged from 35 to 70 dB SL. NH infants needed a higher presentation level to discriminate /ba-da/ than /a-i/, and consistent with the results of Nozza (1987), 29% were unable to discriminate /ba-da/ at the highest presentation level (70 dBA).…”
Section: Introductionmentioning
confidence: 99%